Preparation method of high-entropy alloy film layer
Through multi-target magnetron sputtering technology, the high-entropy alloy film layer is deposited on Ti-6Al-4V substrate, and the high-entropy alloy film layer is solved. The complexity and high defect rate in the production technology have achieved improvements in the uniformity of the film layer and high-temperature oxidation resistance.
Patent Information
- Application Number
- CN202411369689.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
The production technology of high-entropy alloy film layers has problems such as complex preparation process, high defect rate and sensitivity to environmental conditions.
Using multi-target magnetron sputtering technology to deposit Ti-Al-Cr-Si-Ni or Ti-Al-Cr-Si-Nb high-entropy alloy film layer on Ti-6Al-4V substrate, through the vacuum sputtering chamber The power supply of high-purity argon, DC target and radio frequency target are used for sputtering co-deposition, controlling the sputtering temperature and time, and optimizing the grinding and polishing process of the substrate.
The high-entropy alloy film layer has uniform composition and flat surface, good oxidation resistance, low defect rate and strong adaptability to environmental conditions, significantly improving high-temperature oxidation resistance.
Smart Images

Figure CN119265514A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high entropy alloy material preparation, and in particular to a method for preparing a high entropy alloy film layer. Background Art
[0002] High entropy alloys have excellent corrosion resistance, oxidation resistance and high temperature resistance due to their complex structure of multiple principal elements. Especially in the Ti-Al-Cr-Si-X alloy system, the design of the incorporation of Ti, Al, Cr, Si and X elements (such as Nb or Ni) aims to improve the bonding strength between the alloy film and the matrix, and at the same time form a dense oxide layer through the synergistic effect of the elements, effectively blocking the diffusion of oxygen into the matrix, and achieving the purpose of enhancing high temperature oxidation resistance.
[0003] However, the current high entropy alloy film manufacturing technology has problems such as complex preparation process, high defect rate and sensitivity to environmental conditions. In view of these challenges, the present invention proposes a high entropy alloy film preparation method to solve such problems. Summary of the invention
[0004] The present invention aims to provide a method for preparing a high entropy alloy film layer to solve the problems of the existing high entropy alloy film layer manufacturing technology, such as complex preparation process, high defect rate and sensitivity to environmental conditions.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a high entropy alloy film layer comprises the following steps:
[0007] S1, grinding, polishing, cleaning and drying the substrate;
[0008] S2, put the substrate processed in step S1 into a vacuum chamber with a degree of 5×10 -8 Torr in the sputtering chamber, and introduce high-purity argon gas to maintain the working pressure of the sputtering chamber at 3mTorr;
[0009] S3, placing the Ti-Al-Cr-X alloy target on the DC target position of the magnetron sputtering system, and placing the Si target on the RF target position of the magnetron sputtering system;
[0010] S4: Turn on the power of the DC target and the RF target in step S3, and deposit a Ti-Al-Cr-Si-X film layer on the substrate by sputtering co-deposition.
[0011] Further, in step S1, the substrate is a Ti-6Al-4V titanium alloy sheet.
[0012] Furthermore, the size of the substrate is 10 mm×10 mm×1 mm.
[0013] Furthermore, in step S1, the specific method of processing the substrate is:
[0014] First, use 500 mesh, 1000 mesh, 1500 mesh, 2000 mesh, 3000 mesh, and 5000 mesh sandpaper to grind in sequence. After grinding until there are no scratches visible to the naked eye, use a 0.1-0.5μm Al2O3 solution to polish until the surface is bright. Then, ultrasonically clean it in acetone, anhydrous ethanol, and deionized water for 10-20 minutes in sequence, and finally blow dry with nitrogen.
[0015] Further, in step S3, the power supply power of the DC target position is 60W-80W, and the power supply power of the RF target position is 30W-50W.
[0016] Further, in step S4, the sputtering temperature is room temperature, and the sputtering time is 2h-5h.
[0017] Further, in step S4, based on the total number of atoms of Ti-Al-Cr-Si-X, the number of atoms of Ti accounts for 15-25%, the number of atoms of Al accounts for 15-25%, the number of atoms of Cr accounts for 15-35%, the number of atoms of Si accounts for 15-20%, and the number of atoms of X accounts for 20-25%.
[0018] Further, in step S3 and step S4, X is Ni or Nb.
[0019] The beneficial effects of the technical solution are:
[0020] The present invention deposits a Ti-Al-Cr-Si-Ni or Ti-Al-Cr-Si-Nb high entropy alloy film layer on a Ti-6Al-4V substrate based on a multi-target magnetron sputtering technology. The process of the present invention is simple, and the prepared high entropy alloy film layer has uniform composition and a smooth surface, and has good oxidation resistance, a low defect rate and strong adaptability to environmental conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The surface morphology SEM and AFM characterization images of the Ti-Al-Cr-Si-Ni high entropy alloy film prepared in Example 1;
[0022] Figure 2 This is the full XPS spectrum of the Ti-Al-Cr-Si-Ni high entropy alloy film prepared in Example 1 after heat treatment;
[0023] Figure 3 This is a spectrum of TiO2 after heat treatment of the Ti-Al-Cr-Si-Ni high entropy alloy film prepared in Example 1;
[0024] Figure 4This is a spectrum of Al2O3 after heat treatment of the Ti-Al-Cr-Si-Ni high entropy alloy film prepared in Example 1;
[0025] Figure 5 This is a spectrum of Cr2O3 after heat treatment of the Ti-Al-Cr-Si-Ni high entropy alloy film prepared in Example 1;
[0026] Figure 6 This is a spectrum of SiO2 after heat treatment of the Ti-Al-Cr-Si-Ni high entropy alloy film prepared in Example 1;
[0027] Figure 7 This is a SEM characterization image of the surface morphology of the Ti-Cr-Al-Si-Nb high entropy alloy film prepared in Example 2;
[0028] Figure 8 This is a cross-sectional SEM image of the Ti-Cr-Al-Si-Nb high entropy alloy film prepared in Example 2;
[0029] Fig. 9 This is a SEM characterization image of the surface morphology of the Ti-Cr-Al-Si-Nb high entropy alloy film layer prepared in Example 2 after heat treatment;
[0030] Fig.10 This is a morphology comparison diagram of the Ti-Cr-Al-Si-Nb high entropy alloy film prepared in Example 2 and the Ti-6Al-4V substrate after the same heat treatment. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments:
[0032] A method for preparing a high entropy alloy film layer comprises the following steps:
[0033] S1, grinding, polishing, cleaning and drying the substrate;
[0034] Wherein, in step S1, the substrate is a Ti-6Al-4V titanium alloy sheet, and the size of the substrate is 10 mm×10 mm×1 mm;
[0035] Among them, the specific method of processing the substrate is:
[0036] First, use 500 mesh, 1000 mesh, 1500 mesh, 2000 mesh, 3000 mesh, and 5000 mesh sandpaper to grind in sequence. After grinding until there are no scratches visible to the naked eye, use a 0.1-0.5μm Al2O3 solution to polish until the surface is bright. Then, ultrasonically clean it in acetone, anhydrous ethanol, and deionized water for 10-20 minutes in sequence, and finally blow dry with nitrogen.
[0037] S2, put the substrate processed in step S1 into a vacuum chamber with a degree of 5×10 -8 Torr in the sputtering chamber, and introduce high-purity argon gas to maintain the working pressure of the sputtering chamber at 3mTorr;
[0038] S3, placing the Ti-Al-Cr-X alloy target on the DC target position of the magnetron sputtering system, and placing the Si target on the RF target position of the magnetron sputtering system;
[0039] Among them, the power supply power of the DC target is 60W-80W, and the power supply power of the RF target is 30W-50W.
[0040] S4: turning on the power of the DC target and the RF target in step S3, and depositing a Ti-Al-Cr-Si-X film layer on the substrate by sputtering co-deposition;
[0041] The sputtering temperature is 20°C-30°C, and the sputtering time is 2h-5h.
[0042] Wherein, X is Ni or Nb.
[0043] Among them, the atomic number of Ti accounts for 15-25%, the atomic number of Al accounts for 15-25%, the atomic number of Cr accounts for 15-35%, the atomic number of Si accounts for 15-20%, and the atomic number of X accounts for 20-25%.
[0044] Example 1
[0045] like Figure 1 As shown in the figure, the sputtering pressure is set to 3mT, the sputtering time is 5h, the DC target (Ti-Al-Cr-Ni target) power is 60W, the RF target (Si target) power is 50W, and the atomic numbers of Ti, Al, Cr, Ni, and Si account for 23%, 21%, 18%, 21%, and 17%, respectively. It can be seen from the figure that the Ti-Al-Cr-Si-Ni high entropy alloy film layer prepared by the present invention has uniform composition and a smooth surface.
[0046] In order to explore the high temperature anti-oxidation mechanism of the Ti-Al-Cr-Si-Ni high entropy alloy film prepared by the above method, the sample was characterized by XPS to determine the composition of the oxide on the surface of the film. Figure 2The figure shows the XPS full spectrum of the Ti-Al-Cr-Si-Ni high entropy alloy film sample after heat treatment at 800°C for 100h. It can be confirmed that Ti, Al, Cr, Si and O elements exist on the surface of the oxide layer of the film. Since the Ni element in the film cannot be detected, it can be inferred that the Ni element exists inside the oxide layer or that the Ni element does not participate in oxidation. A high-resolution scan is performed near the peak positions of Ti2p, Al2p, Cr2p and Si2p in the XPS full spectrum to obtain a high-resolution spectrum of each element. According to the standard XPS binding energy, Figure 3 It can be seen that the binding energies of Ti2p are 458.2eV and 463.9eV, corresponding to the Ti-O bond, representing TiO2. Figure 4 The Al2p peak at 74.1 eV indicates the presence of Al2O3. Figure 5 It can be seen that the Cr2p peaks at binding energies of 576.7 eV and 586.4 eV are similar to the Cr in Cr2O3. 3+ The standard value is consistent. Figure 6 The Si2p peak can be fitted at a binding energy of 102.2 eV, representing the presence of SiO2. Therefore, it can be inferred that the surface material of the oxide layer of the TiAlCrSiNi high entropy alloy film after heat treatment at 800°C for 100 h is mainly composed of TiO2, Al2O3, Cr2O3 and SiO2.
[0047] According to the theory proposed by Pilling and Bedworth, the density of the oxide film depends on the volume ratio of oxide to metal atoms (PBR), which can be expressed by the following formula:
[0048]
[0049] Where V MO is the volume of the oxide formed, V Mis the volume of metal atoms. When 1 < PBR < 2, the oxide tends to grow into the matrix, promoting the tight combination of the oxide film and the matrix and playing a role in high-temperature oxidation resistance; when PBR < 1, there is tensile stress in the oxide, resulting in an incomplete oxide film without protection; when PBR > 2, the oxide film has a loose structure and is easy to peel off. The PBR value of TiO2 is 1.95. Although it is within the range of 1 - 2, it is already close to 2. The formed oxide film has a loose structure and is relatively easy to crack and peel off. Moreover, TiO2 has a rutile structure at high temperatures. Under higher oxygen partial pressure conditions, oxygen vacancies are its main defects, and O elements are easy to further diffuse into the film layer through oxygen vacancies and continue to react with other elements in the film layer. This is also the reason for the relatively high oxidation weight gain rate in the early stage of the oxidation kinetic curve. The PBR value of Al2O3 is 1.28, which is relatively close to 1. Therefore, the Al2O3 oxide film can completely cover the film layer surface and is not easy to crack. Moreover, Al2O3 and Cr2O3 are corundum-type oxides. In oxides with this structure, ions are closely packed, and the diffusion rate of O elements in them is very small, which can prevent the invasion of external O elements, slow down the oxidation process, and have good protection. Si reacts with O to form dispersed oxide SiO2, effectively filling the vacancies at the interface between the oxide film and the film layer, and also playing a certain role in the internal diffusion of oxygen atoms. Therefore, the formation of dense oxides such as Al2O3, Cr2O3, and SiO2 is the main reason for the high-temperature oxidation resistance of the film layer. The Si element has a repulsive effect on O compared with other elements, and the Si element can reduce the 4+ activity of Ti, thereby hindering the formation of TiO2. When the Si element content is 17.33 at.%, the oxidation activities of Al and Cr elements are correspondingly increased, promoting the rapid formation of a dense oxide film. Therefore, the Ti-Al-Cr-Si-Ni high-entropy alloy film layer prepared in the present invention has good high-temperature oxidation resistance.
[0050] Example 2
[0051] The sputtering gas pressure was set to 3 mT, the sputtering time was 5 h, the power of the DC target position (Ti-Al-Cr-Nb target) was 80 W, the power of the RF target position (Si target) was 50 W, and the atomic number ratios of Ti, Al, Cr, Nb, and Si were: 18%, 15%, 30.5%, 21%, 15.5%, Figure 7 is the scanning electron microscope (SEM) characterization result of the surface morphology of the Ti-Cr-Al-Si-Nb high-entropy alloy film layer. It can be seen from the SEM image that the surface of the Ti-Al-Cr-Si-Nb film layer prepared in the present invention has no obvious defects such as pores, cracks, or particles, and the surface is flat and dense. Figure 8 is the cross-sectional SEM image of the prepared film layer. The film layer thickness is 2.36 μm, the cross-sectional morphology is dense, the thickness is uniform, and there are no hole defects.
[0052] A high temperature oxidation comparison experiment was conducted on the Ti-Cr-Al-Si-Nb high entropy alloy film prepared above and the Ti-6Al-4V substrate:
[0053] The Ti-6Al-4V substrate and the Ti-Cr-Al-Si-Nb high entropy alloy film samples were subjected to a high temperature heat treatment at 600 ° C for 50 h (two groups each) using a muffle furnace (Tianjin Zhonghuan SX-B07123). During this period, a precision electronic balance was used to weigh the samples every 10 h. The results are shown in Table 1:
[0054] Table 1 Mass of Ti-6Al-4V substrate and Ti-Al-Cr-Si-Nb alloy coating before and after heat treatment (g)
[0055]
[0056] Oxidation weight gain rate:
[0057] V = ΔG / S, where ΔG is the weight gain of the sample due to oxidation; S is the surface area of the sample;
[0058] It can be seen from the table that in the first 20 hours, the isothermal oxidation weight gain rate of the Ti-Cr-Al-Si-Nb high entropy alloy film layer showed an increasing trend, but it grew more slowly than that of the Ti-6Al-4V substrate; when the oxidation time was 20-40 hours, the oxidation weight gain of the Ti-6Al-4V substrate still increased at a relatively fast rate, but the oxidation weight gain rate of the Ti-Cr-Al-Si-Nb high entropy alloy film layer gradually decreased; when the oxidation time was 40-50 hours, the oxidation weight gain of the Ti-6Al-4V substrate still increased at a relatively fast rate, while the oxidation rate of the Ti-Cr-Al-Si-Nb high entropy alloy film layer tended to be stable, and its final oxidation weight gain rate was 0.4 mg cm -2 , while the final oxidation weight gain rate of Ti-6Al-4V substrate is 1.6 mg·cm -2, The oxidation resistance of the Ti-Cr-Al-Si-Nb high entropy alloy film prepared by the present invention is improved by 4 times.
[0059] Fig. 9 This is a SEM characterization of the surface morphology of the Ti-Cr-Al-Si-Nb high entropy alloy film layer after heat treatment at 600°C for 50 hours. It can be seen from the figure that the oxide layer of the Ti-Al-Cr-Nb-Si high entropy alloy film layer prepared by the present invention is dense, tightly bonded to the substrate, and no falling off occurs, so its high-temperature oxidation resistance is relatively excellent.
[0060] The Ti-Al-Cr-Nb-Si high entropy alloy film and the Ti-6Al-4V substrate prepared above were heat treated at 800°C for 10 h to analyze their high temperature oxidation resistance:
[0061] The Ti-Cr-Al-Si-Nb high entropy alloy film and Ti-6Al-4V substrate were weighed and measured by a precision electronic balance before and after heat treatment at 800℃ for 10 hours. The average values of the film and Ti-6Al-4V substrate before heat treatment were 2.8987g and 2.67305g, respectively; the weight values of the two after heat treatment were 2.89955g and 2.6743g, respectively. The mass increase of the Ti-6Al-4V substrate was significantly higher than that of the high entropy alloy film. The calculation shows that the oxidation weight gain rate of the Ti-Cr-Al-Si-Nb high entropy alloy film within 10 hours is 0.85mg·cm -2 , while the oxidation weight gain rate of Ti-6Al-4V substrate is 1.25 mg·cm -2 The high-temperature oxidation resistance of the Ti-Cr-Al-Si-Nb high-entropy alloy film after heat treatment at 800℃ for 10h is 1.47 times higher than that of the Ti-6Al-4V substrate. Fig.10 As shown in the figure, after the Ti-6Al-4V substrate was heat treated at 800℃ for 10h (right), the surface oxide film had a small amount of peeling off, while the oxide film on the surface of the Ti-Cr-Al-Si-Nb high entropy alloy film layer was still well bonded to the substrate (left).
[0062] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical schemes or characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical scheme of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a high entropy alloy film, characterized in that: The following steps are involved: S1, grinding, polishing, cleaning and drying the substrate; S2, put the substrate processed in step S1 into a vacuum chamber with a degree of 5×10 -8 Torr in the sputtering chamber, and introduce high-purity argon gas to maintain the working pressure of the sputtering chamber at 3mTorr; S3, placing the Ti-Al-Cr-X alloy target on the DC target position of the magnetron sputtering system, and placing the Si target on the RF target position of the magnetron sputtering system; S4: Turn on the power of the DC target and the RF target in step S3, and deposit a Ti-Al-Cr-Si-X film layer on the substrate by sputtering co-deposition.
2. The method for preparing a high entropy alloy film according to claim 1, characterized in that: In step S1 , the substrate is a Ti-6Al-4V titanium alloy sheet.
3. A method for preparing a high entropy alloy film according to claim 2, characterized in that: The size of the substrate is 10 mm×10 mm×1 mm.
4. The method for preparing a high entropy alloy film according to claim 1, characterized in that: In step S1, the specific method of processing the substrate is: First, use 500 mesh, 1000 mesh, 1500 mesh, 2000 mesh, 3000 mesh, and 5000 mesh sandpaper to grind in sequence. After grinding until there are no scratches visible to the naked eye, use a 0.1-0.5μm Al2O3 solution to polish until the surface is bright. Then, ultrasonically clean it in acetone, anhydrous ethanol, and deionized water for 10-20 minutes in sequence, and finally blow dry with nitrogen.
5. The method for preparing a high entropy alloy film according to claim 1, characterized in that: In step S3, the power supply power of the DC target position is 60W-80W, and the power supply power of the RF target position is 30W-50W.
6. The method for preparing a high entropy alloy film according to claim 1, characterized in that: In step S4, the sputtering temperature is room temperature, and the sputtering time is 2h-5h.
7. The method for preparing a high entropy alloy film according to claim 1, characterized in that: In step S4, based on the total number of atoms of Ti-Al-Cr-Si-X, the number of atoms of Ti accounts for 15-25%, the number of atoms of Al accounts for 15-25%, the number of atoms of Cr accounts for 15-35%, the number of atoms of Si accounts for 15-20%, and the number of atoms of X accounts for 20-25%.
8. The method for preparing a high entropy alloy film according to claim 7, characterized in that: In step S3 and step S4, X is Ni or Nb.